Darbarahi-yi istiqlal va darbarahi-yi shuraha (Shurai-yi Muttahidi Chap barai-yi Dimukrasi va Istiqlal)
On independence and the councils. Quoted from "Payami Azadi" the organ of the Leftist United Council for the Democracy and Independence.